2019
DOI: 10.1038/s41467-019-12186-6
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of HuR in murine skeletal muscle enhances exercise endurance and prevents cancer-induced muscle atrophy

Abstract: The master posttranscriptional regulator HuR promotes muscle fiber formation in cultured muscle cells. However, its impact on muscle physiology and function in vivo is still unclear. Here, we show that muscle-specific HuR knockout (muHuR-KO) mice have high exercise endurance that is associated with enhanced oxygen consumption and carbon dioxide production. muHuR-KO mice exhibit a significant increase in the proportion of oxidative type I fibers in several skeletal muscles. HuR mediates these effects by collabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 68 publications
3
27
0
Order By: Relevance
“…This is a trend that does not hold true for female animals, which show increases in RER relative to controls ( Figure 2 D). HuR m−/− male mice display RER values higher than controls at several time points when fed LFD, continuing to suggest an increased reliance on carbohydrates in agreement with previously reported results [ 6 , 17 ] ( Figure 2 E). No difference is present in RER patterns between genotypes for female animals fed LFD ( Figure 2 F).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This is a trend that does not hold true for female animals, which show increases in RER relative to controls ( Figure 2 D). HuR m−/− male mice display RER values higher than controls at several time points when fed LFD, continuing to suggest an increased reliance on carbohydrates in agreement with previously reported results [ 6 , 17 ] ( Figure 2 E). No difference is present in RER patterns between genotypes for female animals fed LFD ( Figure 2 F).…”
Section: Resultssupporting
confidence: 92%
“…It was previously reported that HuR m−/− mice display increased energy expenditure relative to control animals, indicative of an increased oxidative phenotype in skeletal muscle [ 17 ]. HuR m−/− female mice fed HFD likewise show slightly higher energy expenditure relative to control females, but only during the day period while animals are not as active.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, no selective fiber atrophy has been observed in a study of human patients with upper gastrointestinal or pancreatic cancer (30 men and 11 women) [ 51 ]. In a recent study [ 52 ] linking the RNA-binding protein, HuR, to fiber type specification demonstrates that while type 1 fiber-rich soleus muscle of male wild-type mice bearing the Lewis lung carcinoma was significantly wasted, muscle in the muscle-specific HuR knockout mice was preserved. The mechanism underlying the protective effect is through enrichment of type 1 fibers by HuR collaborating with the mRNA decay factor KSRP to destabilize PGC-1a mRNA.…”
Section: Sex-related Muscle Fiber Composition In Cancer Cachexiamentioning
confidence: 99%
“…Muscle atrophy is characterized by a decreased contractility of muscle fibers, changes in muscle fiber types and myosin subtypes, and a net loss of cytoplasm, organelles, and total proteins (Dumitru et al, 2018). In recent years, although research on denervated muscle atrophy has made substantial progress, it has mainly focused on single events, genes, or proteins (Li et al, 2017;Reza et al, 2017;Gueugneau et al, 2018;Yin et al, 2018;Castets et al, 2019;Janice Sánchez et al, 2019). Because systematic research on denervated muscle atrophy has not yet been conducted, no breakthrough has been achieved.…”
Section: Introductionmentioning
confidence: 99%